PERBANDINGAN ASPEK ONTOLOGI DAN EPISTEMOLOGI ILM AL-MA’ANIY DAN PRAGMATIK - Fauzi, Moch. Sony (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
The Ma’aniy and Pragmatics are two field of study that is closely related to language. Both of them have different background. The Ma’aniy was born from the intention to discover the miracle of Qur’an from its language. On the other hand, pragmatics was born from the study of language phenomena in the forms of human utterances. The ma’aniy was born in eastern world, and pragmatics was from the west. Through contrastive analytic and conventional text study this paper is aimed at comparing the epistemological aspects of those two field of study, especially at three different aspects of pragmatics, theory of speech act, implicature and relevance. Those three aspects are found out the similarities with the aspects in ma’aniy. The findings are first, ontologically, there is similarity between ma’aniy and pragmatics, especially in discussing the forms and meaning of speech that is influenced by speech context. Many definitions of those two field of studies have similarities. Second, epistemologically, those two field of studies have similarities, for example, in ma’aniy there is “kalam khabariy” and “kalam insya’iy”, that is similar to the maxim violation in the speech implicature in pragmatics.